2012
DOI: 10.1111/j.2044-8333.2012.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrorists' personal constructs and their roles: A comparison of the three Islamic terrorists

Abstract: It is hypothesized that individuals who play different roles in terrorist organizations will have different psychological processes underlying their activities. An innovative examination of the personal construct systems of terrorists explored this. As part of a larger study, three individuals convicted of Islamic‐related terrorist violence in India were interviewed using a semi‐structured life narrative procedure enhanced by a Repertory Grid (Kelly, 1955/1991). One was a senior leader of a terrorist group, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…As in various previous studies (Turpin, Dallos, Owen, & Thomas, 2009;Yorke & Dallos, 2015;Winter, 2016bWinter, , 2018, including an investigation of "Jihadi terrorists" in India (Canter, Sarangi, & Youngs, 2014;Sarangi, Canter, & Youngs, 2013), the present research has indicated the complementarity of a relatively unstructured interview procedure with repertory grid technique, the former providing particular insight into processes, and the latter into features of the structure and content, of construing. The grid measures concerning construct structure provided a less consistent picture than most of those concerning the construing of particular elements, and may require refinement and exploration in further research.…”
Section: Methodssupporting
confidence: 69%
“…As in various previous studies (Turpin, Dallos, Owen, & Thomas, 2009;Yorke & Dallos, 2015;Winter, 2016bWinter, , 2018, including an investigation of "Jihadi terrorists" in India (Canter, Sarangi, & Youngs, 2014;Sarangi, Canter, & Youngs, 2013), the present research has indicated the complementarity of a relatively unstructured interview procedure with repertory grid technique, the former providing particular insight into processes, and the latter into features of the structure and content, of construing. The grid measures concerning construct structure provided a less consistent picture than most of those concerning the construing of particular elements, and may require refinement and exploration in further research.…”
Section: Methodssupporting
confidence: 69%
“…Narratives and counternarratives already feature in the body of research on terrorism and violent political extremism. 8 By and large, however, this solely concerns the message that acts of terror and political violence convey or with which they are accompanied. This is an important area of research, but the relevance of narrative research is considerably broader than these explicit political stories.…”
mentioning
confidence: 99%
“…Canter et al [31], reported that a terrorist they interviewed was unaware he was a bomb carrier. He was instructed to drive a car and park it in a busy market, he exited the vehicle and it detonate, killing dozens.…”
Section: Discussionmentioning
confidence: 99%
“…Canter et al [31] could have included a more detailed account of the terrorist's personal constructs which may have allowed researchers a more in depth exploration of their motivation to support terrorist acts and their perception of themselves as a person and their role within the organization. An exploratory interview conducted outside of the prison, free of distraction would produce better results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation